Implications of Access to Portable Water on Child Health Production in Cameroon - Mbu Daniel Tambi; Peter Arung Etta (International Journal of Business Economics (IJBE), 2022)
This study attempts to quantify the effects of access to portable water on child health outcome and to investigate potential heterogeneities in the effect of access to portable water on child health by age distribution. Methodologically, we used the 2011/2018 Cameroon demographic and health survey via 2SLS and ivprobit models. Results show that a positive marginal change in access to portable water will result to a corresponding increase in child health, Child health of age 24-36 months is strongly affected by access to portable water. Decision makers should intensify child health access to portable water campaigns, following the WHO standards.